Rancang Bangun Sistem Pendeteksi Kesamaan Tugas Kuliah - Akbar Hanafi Siregar; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Document digitalization is expected in this modern era. However, there are so many positive and negative impacts caused by document digitalization. One of the negative impacts of digitizing documents is the high number of cheating cases in the assignment made by students. For that so, a solution to this high number of cheating cases needs to be found. Detection of the similarity of documents is one of many solutions to find out student fraud in doing the assignment. To find out the level of document similarity, a system that can detect the similarity of documents needs to be made. String matching is a method that is quite often used in building a system that can detect the level of similarity of documents. To ensure that the system has a good accuracy, several stages of testing the system need to be carried out. In this study, testing was carried out using three student assignments documents as the test data by detecting the level of similarity between each document. After several testing stages, the result shows that the highest similarity percentage is at 75.89% from comparing documents assignment one and assignment two, while the lowest similarity percentage is at 34.81% from comparing documents assignment three and assignment 1.Keyword: Similarity, String Matching, Assignments Documents.